Association between abortion restrictiveness and suicidality among birthing people in the United States 2010 to 2020 - Platt, I. S.; Zivin, K.; Xiaosong, Z.; Tilea, A.; Miller, E.; Widner, A.; Courant, A.; Hall, S. V.; Schroeder, A.; Dalton, V. K. (Frontiers in Reproductive Health, 2025)
IntroductionPrior research found that suicidality increased among commercially insured birthing people between 2006 and 2017. The 2022 Dobbs v. Jackson Women's Health Organization decision overturned Roe v. Wade and made obtaining an abortion more difficult across the United States, which may have negative mental health effects among commercially insured birthing people.MethodsWe conducted a cross-sectional analysis using mixed-effects logistic regression models to quantify the relationship between state-level abortion restrictions and a diagnosis of suicidality or self-harm in the 12 months before or after delivery among individuals with employer-sponsored health insurance in the United States who delivered between 2010 and 2020.ResultsOf the 610,177 deliveries in our final analytic cohort, birthing people residing in states with high abortion restrictiveness were younger (12.8% of birthing people were ages 15–24 compared to 7.8% in low restriction states) and more likely to be Black (10.4% compared to 6.1%). Birthing people living in states with high abortion restrictiveness were more likely to experience suicidality than birthing people living in states with low abortion restrictiveness [odds ratio (OR): 1.5; 95% CI: 1.2, 1.8; p = 0.0012]. When controlling for age, state abortion restrictiveness was not significantly associated with suicidality [adjusted odds ratio (adjOR): 1.2; 95% CI: 1.0, 1.4; p = 0.0603], and birthing people ages 15–24 were substantially more likely than birthing people ages 35–44 to experience suicidality (adjOR: 7.3; 95% CI: 6.5, 8.2; p < 0.001).ConclusionIn the years prior to the Dobbs decision, commercially insured birthing people in states with high abortion restrictiveness experienced a growing mental health crisis, when compared to those in low restriction states. These differences are associated with differences in demographic characteristics, such as age and race. As researchers continue to monitor health outcomes related to the recent enactment of the most severe category of restriction (e.g., bans), these findings remain crucial to recognize and account for in further studies.